2005
DOI: 10.1055/s-2004-830544
|View full text |Cite
|
Sign up to set email alerts
|

Tumour-Like Inflammatory Abdominal Conditions in Children

Abstract: The presence of a tumour, poor general condition, features of anaemia, increased erythrocyte sedimentation rates and imaging suggesting malignancy were the common features in 4 different tumour-like abdominal conditions that are extremely rare in childhood. These conditions included: extensive retroperitoneal tumour with rib involvement that turned out to be an inflammatory lesion caused by Actinomyces in a 12-year-old girl; multi-loculated tumour of the mesentery/ovary caused by mesenteric lymphadenopathy in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…In children, abdominal infection caused by Actinomyces bacteria is rare. In a review of the English literature, we identified only 12 reports of children with abdominal AMC [6][7][8][9][10][11][12][13][14][15][16][17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In children, abdominal infection caused by Actinomyces bacteria is rare. In a review of the English literature, we identified only 12 reports of children with abdominal AMC [6][7][8][9][10][11][12][13][14][15][16][17].…”
Section: Discussionmentioning
confidence: 99%
“…We present the case of a 13-year-old adolescent boy with appendiceal AMC who was admitted with right lower abdominal pain to our institution. In the English literature, we have found only 12 reports of patients with abdominal AMC [6][7][8][9][10][11][12][13][14][15][16][17]. In this article, the rare occurrence of AMC in a child is discussed, and the English literature on that disorder is briefly reviewed.…”
mentioning
confidence: 95%
“…It rarely causes disease (5). Actinomycosis may affect the cervicofacial, mediastinal, abdominal or pelvic regions (1,(6)(7)(8)(9)(10). The main step in the pathogenesis of actinomycosis is interruption of the mucocutaneus barriers leading to suppuration and abscess formation.…”
Section: Discussionmentioning
confidence: 99%
“…These cases ranged from a 2.5-year old girl with mesenteric lymphadenopathy to a 42-year-old woman with a history of Salmonella osteomyelitis of the fifth vertebra. [5][6] Multiple cases reported infection in patients with a history of recent gastrointestinal distress, systemic lupus erythematosus (SLE) or endometriotic lesions. 3,7-8 Indeed, our patient had undiagnosed endometriotic ovarian cysts as reported on the final pathology report.…”
Section: Commentmentioning
confidence: 99%